Pomoc finansowa Unii Europejskiej w rozwoju regionalnym Grecji - jej skala i efekty - Wilk, Kazimiera; Derlukiewicz, Niki (The EU financial aid and regional development in Greece - its scale and effects, 2006)
Strengthening social and economic cohesion is one ofthe most important priorities in the European Union. In this connection very essential is regional policy and its measures especially structural funds and the Cohesion Fund. The main aim ofthe EU aid is to level disproportions of development among regions. Greece has received notable aid from the European Regional Development Fund for years. In this paper determinants and amounts ofthe EU aid were discussed. Moreover, the authors provided an evaluation of using the EU funds in Greece.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 42-53